The Effect Of Product Display, Product Completeness, And Price On Repeat Purchase Interest With Consumer Satisfaction As An Intervening Variable (Case study on Batik Ningrat Lasem): Pengaruh Tampilan Produk, Kelengkapan Produk, dan Harga terhadap Minat Pembelian Ulang dengan Kepuasan Konsumen sebagai Variabel Intervening (Studi Kasus pada Batik Ningrat Lasem) - Putri, Nuraini; Heri Prabowo; Henry Goeltom (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the Influence of Product Display, Product Completeness, and Price on Repurchase Intention with Consumer Satisfaction as an Intervening Variable (Case Study on Batik Ningrat Lasem). The population in this study were buyers of Batik Ningrat Products in Rembang City. The sampling technique used was the non-probability sampling technique. In this study, the sample used was 97 respondents. The data analysis technique used in this study is SEM to process data with calculations using Smart PLS 4.0 software. The results of the analysis and discussion showed that partially Electronic Word Of Mouth had a positive and significant effect on Consumer Buying Decisions on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch. Partially, Price has a positive and significant effect on Consumer Buying Decisions on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch. Partially Brand Image has a positive and significant effect on Consumer Buying Decision on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch Product display does not affect consumer satisfaction. Product completeness does not affect consumer satisfaction. Price has a positive and significant effect on consumer satisfaction. Product display has a positive and significant effect on repurchase interest. Product completeness does not affect repurchase interest. Price does not affect repurchase interest. Consumer satisfaction has a positive and significant effect on repurchase interest. Product display does not affect repurchase interest through consumer satisfaction. Product completeness does not affect repurchase interest through consumer satisfaction. Price does not affect repurchase interest through consumer satisfaction on Batik Ningrat Lasem products.